Experience of Menopausal Symptoms and Perception of Menopause among Women at Bharatpur Chitwan Nepal: - Ranabhat, Mina Kumari; Thapa, Basanta; Neupane , Sarmila; Pokheral, Manju (Birat Journal of Health Sciences, 2025)
Introduction: Menopause is a natural biological process in women’s life which occurs commonly between the ages of 45-55 years worldwide. The mean age of menopause was 48.02 years. Objectives: The objective of the study are to assess the experience of menopausal symptoms,level of perception of menopause and to find out the association between level of perception and selected variables. Methodology: A cross-sectional study design was conducted by using non probability convenience sampling technique with structured interview schedule among 425 women between the age group 45 to 60 years in Bharatpur, Chitwan. The collected data entered in IBM SPSS version 20 and analyzed by descriptive and inferential statistics. Results: Out of 425 respondents, 57.4% respondents belong to the age group more than 50 years. Among them, 67.7% of respondents became menopause with the mean age 48.93 years and standard deviation was 3.21. Most of the respondents experienced all types of symptoms vasomotor, physical, psycho-social and sexual. Among these symptoms within vasomotor 58.6% has hot flashes, in physical 76.9% feeling lack of energy, in psycho-social 65.9% experience sleep disturbances and in sexual 60.7% change sexual desire. Only 32.5% of respondents shared their symptoms with family. In present study, 75.5% of respondents had positive attitude towards menopause. Conclusion: Based on the findings of the study, it is concluded that every women suffer from menopausal symptoms but they could not share to their family. Raising the awareness programme on menopausal symptoms in community level that can be managed and prevented sufferings.